Language Rights in a Changing China A National Overview and Zhuang Case Study - Grey, Alexandra (Contributions to the sociology of language ;, 2021)
China has had constitutional minority language rights for decades, but what do they mean today? Answering with nuance and empirical detail, this book examines the rights through a sociolinguistic study of Zhuang, the language of China's largest minority group. The analysis traces language policy from the Constitution to local government practices, investigating how Zhuang language rights are experienced as opening or restricting socioeconomic opportunity. The study finds that language rights do not challenge ascendant marketised and mobility-focused language ideologies which ascribe low value to Zhuang. However, people still value a Zhuang identity validated by government policy and practice. Rooted in a Bourdieusian approach to language, power and legal discourse, this is the first major publication to integrate contemporary debates in linguistics about mobility, capitalism and globalization into a study of China's language policy. The book refines Grey's award-winning doctoral dissertation, which received the Joshua A. Fishman Award in 2018. The judges said the study "decenter[s] all types of sociolinguistic assumptions." It is a thought-provoking work on minority rights and language politics, relevant beyond China.